METHODS OF TEACHING OF THE RUSSIAN LANGUAGE IN THE KARAKALPAK PRIMARY SCHOOL - Khodjaniyazova, A.A. (SCIENCE and SOCIETY, 2024)
The article discusses the methodology of teaching the Russian language in primary classes with Karakalpak as the language of instruction, teaching begins with letter-sound, explanation of new words. The ability to listen and understand simple Russian speech, the ability to pronounce Russian words, perform syllabic and sound-letter analysis, the ability to correctly pronounce Russian sounds, initial sentence construction skills, stress, intonation - all this is acquired by the student during the period of learning to read and write.
Keywords: Russian language; methodology; lesson; teaching; grammaticalization; letters; sounds; Russian literacy; Russian as a foreign language; listening; reading